Blood flow augmentation by intrinsic venular contraction in vivo - Dongaonkar, Ranjeet M. (American Physiological Society, 2012)
Venomotion, spontaneous cyclic contractions of venules, was first observed in the bat wing 160 years ago. Of all the functional roles proposed since then, propulsion of blood by venomotion remains the most controversial. Common animal models that require anesthesia and surgery have failed to provide evidence for venular pumping of blood. To determine whether venomotion actively pumps blood in a minimally invasive, unanesthetized animal model, we reintroduced the batwing model. We evaluated the temporal and functional relationship between the venous contraction cycle and blood flow and luminal pressure. Furthermore, we determined the effect of inhibiting venomotion on blood flow. We found that the active venous contractions produced an increase in the blood flow and exhibited temporal vessel diameter-blood velocity and pressure relationships characteristic of a peristaltic pump. The presence of valves, a characteristic of reciprocating pumps, enhances the efficiency of the venular peristaltic pump by preventing retrograde flow. Instead of increasing blood flow by decreasing passive resistance, venular dilation with locally applied sodium nitroprusside decreased blood flow. Taken together, these observations provide evidence for active venular pumping of blood. Although strong venomotion may be unique to bats, venomotion has also been inferred from venous pressure oscillations in other animal models. The conventional paradigm of microvascular pressure and flow regulation assumes venules only act as passive resistors, a proposition that must be reevaluated in the presence of significant venomotion.